Origin and Evolution of Diploid and Allopolyploid Camelina Genomes Were Accompanied by Chromosome Shattering. Issue 11 (28th August 2019) - Mandáková, Terezie; Pouch, Milan; Brock, Jordan R.; Al-Shehbaz, Ihsan A.; Lysak, Martin A.
Abstract : Camelina allopolyploid genomes originated through recurrent hybridization between two paleogenomes; descending dysploidies in Camelina were accompanied by complex chromosome shattering. Abstract: Complexes of diploid and polyploid species have formed frequently during the evolution of land plants. In false flax ( Camelina sativa ), an important hexaploid oilseed crop closely related to Arabidopsis ( Arabidopsis thaliana ), the putative parental species as well as the origin of other Camelina species remained unknown. By using bacterial artificial chromosome–based chromosome painting, genomic in situ hybridization, and multi-gene phylogenetics, we aimed to elucidate the origin and evolution of the polyploid complex. Genomes of diploid camelinas ( Camelina hispida, n = 7; Camelina laxa, n = 6; and Camelina neglecta, n = 6) originated from an ancestral n = 7 genome. The allotetraploid genome of Camelina rumelica ( n = 13, N 6 H) arose from hybridization between diploids related to C. neglecta ( n = 6, N 6 ) and C. hispida ( n = 7, H), and the N subgenome has undergone a substantial post-polyploid fractionation. The allohexaploid genomes of C. sativa and Camelina microcarpa ( n = 20, N 6 N 7 H) originated through hybridization between an auto-allotetraploid C. neglecta –like genome ( n = 13, N 6 N 7 ) and C. hispida ( n = 7, H), and the three subgenomes have remained stable overall since the genome merger. Remarkably, the ancestral and diploid Camelina genomes were shaped by complex chromosomal rearrangements, resembling those associated with human disorders and resulting in the origin of genome-specific shattered chromosomes.